The Pauline Sense of the Expression “Now the Lord is the Spirit” (2 Cor. 3:17a) - García Serrano, Andrés 1972- (2016)
Because most scholars have limited themselves exclusively to the identification of the Lord in 2 Cor. 3:17a, “Now the Lord is the Spirit”, their studies have failed to understand the relationship between that Lord and the Spirit. This short study explicates the relationship that Paul establishes between the meaning signified by the nouns “Lord” and “Spirit.” In particular, it will address the issue of how the Lord and the Spirit are interrelated by contextualizing the statement in the Pauline Corpus, and will expound upon the dynamic relationship that Paul proclaims in this controversial verse.
Keywords: Christianity; God; letter of recommendation; Moses’ veil; New Covenant; Pauline Christology; Pauline churches; Pauline pneumatology; Religions; Spirit; Transformation